Pelvic veins ultrasound changes after surgical correction in patients with pelvic congestion syndrome - B. S. Havrylenko; A. O. Nykonenko (Patologìâ)
Pelvic congestion syndrome is a form of varicose disease, which is considered to be one of the main causes of chronic pelvic pain in women, which is associated with a violation of pelvic veins hemodynamics.